Numerical Investigation of Vortex-Induced Vibrations of a Rotating Cylinder near a Plane Wall - Ran Li; Jie Gong; Wei Chen; Jie Li; Wei Chai; Chang-kyu Rheem; Xiaobin Li (Journal of Marine Science and Engineering, 2023)
Numerical simulations are carried out to investigate the vortex-induced vibrations of a two-degree-of-freedom (2DOF) near-wall rotating cylinder. Considering the effects of gap ratio, reduced velocity and rotational rate, the amplitude response, wake variations and fluid forces are analyzed, with the Reynolds number of 200 and the mass ratio set to 1.6. The correlative mechanism in the wake–hydrodynamics–vibration is revealed. The results show that the influence of the wall dominates the vortex-induced vibration of the cylinder. The effect of the wall on the vibration weakens as the gap ratio increases, and the effect of the wall on the vibration is negligible when H/D > 1.1. The forward rotation of the cylinder enhances the wall effect, while the backward rotation presents the reverse effect. The vortex-induced vibration of the cylinder is suppressed when 0 < α < 1, and the amplitude range is concentrated at Vr ∈ (3, 5). The wake mode can be divided into five modes, and the wake modes are clarified under different rotation rates and reduced velocities.